Thomas Bain, road building and the Zwartberg Pass : with particular emphasis on socio-economic and civil engineering aspects in the Southern Cape, c.1843-1962 - Goetze, Timothy Mark (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1993.